2012
DOI: 10.1021/ja308132z
|View full text |Cite
|
Sign up to set email alerts
|

Designing Two Self-Assembly Mechanisms into One Viral Capsid Protein

Abstract: A structural fusion protein of the thermally-responsive elastin-like polypeptide and a viral capsid protein (ELP-CP) was designed and the assembly properties were investigated. Interestingly, this protein-based block copolymer could be self-assembled via two mechanisms into two different, well-defined nanocapsules: (1) pH-induced assembly yielded 28 nm virus-like particles and (2) ELP-induced assembly yielded 18 nm virus-like particles. The latter were a result of the emergent properties of the fusion protein.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
123
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(127 citation statements)
references
References 33 publications
3
123
0
Order By: Relevance
“…In this work, we used the truncated mutant (1–149 a.a.) of HBVC subunit, which reportedly prefers the T = 4 symmetry upon capsid formation 18. Interestingly, it is notable that the assembly symmetry of eGFP in ‐HBVCs depended on the linker length: when n = 0, the capsid with T = 4 symmetry was formed, but when n = 4 or 14, the capsid takes smaller structures with T = 3 symmetry ( Table 1 and Figure 1a–c), which indicates that depending on genetic modification of interior space of the capsid, the capsid subunits are self‐assembled through different symmetry to form differently sized nanoparticles, as reported previously 19…”
Section: Resultssupporting
confidence: 74%
“…In this work, we used the truncated mutant (1–149 a.a.) of HBVC subunit, which reportedly prefers the T = 4 symmetry upon capsid formation 18. Interestingly, it is notable that the assembly symmetry of eGFP in ‐HBVCs depended on the linker length: when n = 0, the capsid with T = 4 symmetry was formed, but when n = 4 or 14, the capsid takes smaller structures with T = 3 symmetry ( Table 1 and Figure 1a–c), which indicates that depending on genetic modification of interior space of the capsid, the capsid subunits are self‐assembled through different symmetry to form differently sized nanoparticles, as reported previously 19…”
Section: Resultssupporting
confidence: 74%
“…Materials such as viral capsids 57 and amyloid fibers 58 present examples of such natural assemblies that can be exploited as templates. Engineered repeat proteins can be used as modular platforms for controlling the placement of functional groups, 59 and attachment to a rigid a-helix backbone can control the spacing between organic chromophores.…”
Section: Proteins As Templates For Self-assemblymentioning
confidence: 99%
“…61 In some cases it has been observed that functionalization of the template protein causes self-assembly into a different structure, suggesting that in some cases the free energy of template assembly may not dominate system behavior. 57 Rodlike viral capsids, including the M13 bacteriophage and the tobacco mosaic virus (TMV), have also inspired the design of a large number of materials, starting with early investigations of these capsids as model rodlike particles capable of self-assembly into nematic and smectic liquid-crystalline phases. 62 These viruses have since been developed into versatile platforms for the templated growth and assembly of a wide variety of inorganic and organic molecules.…”
Section: Proteins As Templates For Self-assemblymentioning
confidence: 99%
“…van Eldijk et al have prepared dual-responsive nanoparticles by using a genetically engineered block copolymer of ELP and viral capsid protein, which assembled into virus-like nanocapsules in response to pH and temperature. 108 Research by Callahan et al yielded a tripleresponsive ELP block copolymer system that formed nanoscale spherical micelles (R h $ 30 nm) above the CMT ($ 35 C) in presence of Zn 2þ at pH ¼ 7:4. The ELP block copolymers in the micelles were shown to revert back to individual molecules when the pH was decreased to 6.4, a condition present in solid tumors.…”
Section: Elps For Systematic Delivery Of Chemotherapeuticsmentioning
confidence: 99%